Edith Wharton and the politics of race - Kassanoff, Jennie Ann (Cambridge University, 2013)
Edith Wharton feared that the "ill-bred," "foreign," and poor would overwhelm what was known as the American native elite. Drawing on a range of turn-of-the-century social documents, unpublished archival material, and Wharton's major novels, Jennie A. Kassanoff argues that a fuller appreciation of American culture and democracy becomes available through a sustained engagement with these controversial views. She pursues her theme through Wharton's spirited participation in a variety of turn-of-the-century discourses - from euthanasia and tourism to pragmatism and Native Americans - to produce a truly interdisciplinary study of this major American writer. Kassanoff locates Wharton squarely in the middle of the debates on race, class, and democratic pluralism at the turn of the twentieth century. Drawing on diverse cultural materials, she offers close interdisciplinary readings that will be of interest to scholars of American literature and culture.